Induction of cerebellar cortical neurogenesis immediately following valproic acid exposure in ferret kits - Kamiya, Shiori; Kobayashi, Tetsuya; Sawada, Kazuhiko (Frontiers in Neuroscience, 2023)
Introduction Valproic acid (VPA) is an anticonvulsant/antiepileptic drug that regulates neurogenesis. Its effects vary depending on the timing of exposure and the types of neural progenitors involved. Neonatal exposure to VPA causes autism spectrum disorder-like behaviors in some mammalian species, including ferrets. Ferrets experience the cerebellar cortical histogenesis during early postnatal period. However, no studies have evaluated the effect of VPA on cerebellar corticohistogenesis. The present study aimed to determine the effects of VPA exposure on the developing cerebellar cortex in ferret kits with a particular focus on the cortical neurogenesis. Methods The experimental kits each received an intraperitoneal injection of VPA, 200 μg/g body weight, on postnatal days 6 and 7. EdU and BrdU were administered on postnatal days 5 and 7, respectively, to label cells proliferating prior to and following exposure to VPA. Results We found that 2 h post BrdU injection, BrdU-labeled cells were abundantly distributed in the internal granular layer (IGL), whereas EdU-labeled cells were primarily relegated to the inner pre-migratory zone of the external granular layer (EGL). The density of BrdU-single-labeled cells was significantly lower in the EGL and significantly higher in the IGL of the VPA-exposed group, as compared to the control group. Immunostaining for doublecortin, a marker of immature neurons, was observed in BrdU-single-labeled cells in the IGL of the VPA-exposed group, which was significantly higher than that observed in the control group. EdU-single-labeled cells that had proliferated prior to VPA exposure were also detected in the IGL. While the cell density remained unchanged, significant changes were observed in the proportions of EdU-single-labeled cells immunostained with marker antigens; higher proportion of PCNA immunostaining, but lower proportion of S100 immunostaining in the VPA-exposed group compared to the control group. Discussion These findings suggest the presence of progenitors in the IGL of the developing cerebellar cortex in ferret kits. We called them “internal granular progenitors.” The progenitors may proliferate in response to VPA, leading the differentiated lineage more toward neurons than to glial cells. Thus, VPA may facilitate the differentiative division of internal granular progenitors to produce cerebellar granular neurons.